Reservoir Physical Properties and Micropore Nanocharacteristics of Cores in the Shihezi Formation, Sudong District, Sulige Gas Field, Ordos Basin - Xin Zhang; Feng Wang; Shuyi Liang; Qintao Guo; Jingchun Tian; Bingyue Shen (International Journal of Analytical Chemistry)
Sulige gas field is a very complex large-scale gas field with low porosity, low permeability, low abundance, and strong heterogeneity. In this study, the nanopore structure of the reservoir in the study area was analyzed. The analysis of reservoir physical properties and core microscopic pore characteristics of Shihezi formation in Sudong District, Sulige gas field, Ordos Basin, was put forward. According to core observation, thin section identification, and grain size analysis, the lithology of gas reservoirs in Shan-1 member and He-8 member in the study area is mainly lithic sandstone, lithic quartz sandstone, and quartz sandstone. According to the analysis of physical data in the study area, the reservoirs in Shan-1 member and He-8 member have typical characteristics of low porosity and low permeability. According to that microscopic observation of sandstone thin section and cast thin section combined with the analysis of scan electron microscope, the results show that both Shan-1 member and He-8 member of Sudong area 2 in Sulige gas field are dominated by class I reservoirs and class II reservoirs. Especially, class I reservoirs are widely distributed, with the cumulative area of this type of reservoirs accounting for 70.12% of the total area in Shan section and 64.12% in He-8 section. Class I reservoirs are scattered in the study area, accounting for 0.27% of the total area in the mountain section and 0.36% in the He-8 section. Class IV reservoirs are distributed dispersedly and have a small distribution area. The cumulative area of reservoirs in mountain section accounts for 5.38% of the total area and that in He-8 section accounts for 5.46%. Therefore, Sudong area 2 in Sulige gas field is a typical low porosity and low permeability reservoir. On the basis of geological background, sedimentary microfacies, diagenesis, and pore structure characteristics of the study area, it is considered that the pore structure of sandstone in the study area is mainly controlled by sedimentary characteristics and diagenesis of sandstone.